How to win at the ecology game 1 - Botkin, Daniel B. (Henry Stewart Talks, 2021)
Ecology, Competitive exclusion principle, Species diversity, Diverse environmental conditions, Niches, Symbiosis, Predation, latitude moderate disturbances affect biodiversity